The Future of Local Administration in the Kingdom of Saudi Arabia: An Application to the Najran Region - Ezz Elden, Abdel-Moneim (The Arab Journal of Administration, 2020)
This study aims to develop a conceptual model to be a general framework for the future of the local administration in Saudi Arabia, reflecting its ability to adopt a new vision with new innovative roles that respond to current and future changes, to meet its mission and realize the welfare of local communities. In line with the vision of the Kingdom (2030), the study presents and discusses the components of the proposed model and requirements of its application in the Najran region. This framework is formed as a conceptual design of overlapping systems that are integrated into each other to shape the present and future local administration. The study proposed a vision for the future of the local administration, which includes five main systems: The system of empowering local bodies to set priorities for local development and promote their future functions. The partnering system to create the conditions for partnerships with local components and mobilize the full potential of the community through institutional organizations that handle development projects. The financial system to mobilize domestic resources, attract, and mobilize economic resources in pursuit of greatest benefit to society. A new functional system to break out of the traditional work circle and expand the role of local units in bringing about the desired development. The technical system to keep pace with the rapid and successive changes, to positively interact with the technical changes and improve the ability for better performance.